2012
DOI: 10.1227/neu.0b013e31822d274d
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Analysis of Stenting in Symptomatic Intracranial Atherosclerosis

Abstract: BESs have periprocedural complication rates similar to those of SESs. Less posttreatment stenosis was associated with lower rates of mid-term restenosis. Future randomized trials comparing BESs and SESs may help to identify the stent type that is safest and most durable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 20 publications
1
44
2
Order By: Relevance
“…Our results are comparable with the recent data (1-month stroke and/or death rate of 4.4%-6.2%) derived from some high-volume centers (Ͼ100 cases per year). [17][18][19] A retrospective analysis of 96 patients treated with intracranial angioplasty and stent placement at 3 university-affiliated institutions in the United States reported that the overall 1-month stroke and/or death rate was 7.2% in the 69 SAMMPRIS-eligible group and 7.4% in the 27 SAMMPRIS-ineligible group. 20 The 30-day stroke and/or death rate was 3.3% and 10.2% in the SAMMPRIS-eligible, angioplasty-treated subgroup and the stent-treated subgroup, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are comparable with the recent data (1-month stroke and/or death rate of 4.4%-6.2%) derived from some high-volume centers (Ͼ100 cases per year). [17][18][19] A retrospective analysis of 96 patients treated with intracranial angioplasty and stent placement at 3 university-affiliated institutions in the United States reported that the overall 1-month stroke and/or death rate was 7.2% in the 69 SAMMPRIS-eligible group and 7.4% in the 27 SAMMPRIS-ineligible group. 20 The 30-day stroke and/or death rate was 3.3% and 10.2% in the SAMMPRIS-eligible, angioplasty-treated subgroup and the stent-treated subgroup, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial PTAS emerged as a valuable tool for patients refractory to medical therapy. 16,17 In the PTAS procedure, the operators select the size of the balloon or stent on the basis of the reference vessel diameter during luminal imaging. However, for the patients with NR, sizing of the balloon may not take into account the diminished outer wall diameter and may increase the risk of vessel injury or even rupture when the balloon is inflated.…”
Section: Discussionmentioning
confidence: 99%
“…24 Another recent multicenter report of 670 treated lesions found Mori A lesions were safer to treat (OR, 0.31; 95% CI, 0.13-0.72; PϽ0.007) and were less likely to develop restenosis (OR, 0.33; 95% CI, 0.21-0.55; Pϭ0.0001). 25 We do not know how lesion morphology affected the short-term outcome in the SAMMPRIS cases and what that effect will be on the long-term stroke risk.…”
Section: T He Initial Results Of the Stenting And Aggressive Medicalmentioning
confidence: 99%